Abstract ID: 135 Characterization of an X-ray source based on laser-target interaction using the Geant4 Monte Carlo toolkit. (October 2017) - Pisciotta, Pietro; Russo, Giorgio; Pandola, Luciano; Gizzi, Leonida A.; Labate, Luca; Lamia, Debora; Panetta, Daniele; Russo, Paolo
Abstract : The aims of our work was to design, study and optimize the main characteristics of an X-ray bremsstrahlung source based on a laser-driven electron beam accelerated via Laser Wake-Field Acceleration. This study is performed using a custom Monte Carlo-Geant4 application, called IORT-Laser-therapy. The X-ray source is designed on top of the laser-driven electron accelerator already running at the Intense Laser Irradiation Laboratory of the INO-CNR in Pisa. It is based upon a 10 TW laser system delivering <40 fs duration pulses with >400 mJ energy at a 10 Hz repetition rate. This accelerator has been already proved to be able to deliver electron bunches with up to around 80 MeV with energy spread down to around 25% and bunch charge ranging from few tens of pC up to few nC. Electron interactions are simulated, starting form an exponentially decreasing e- energy spectrum; a thin tungsten foil has been used in order to generate X-rays via bremsstrahlung. The Monte Carlo application allows studying many features of the resulting X-ray beam such as (i) the conversion efficiency using different foil thicknesses, (ii) the X-ray source size (iii) the particle contamination of the output beam, (iv) the out-of-beam scattered radiation for external shielding design. The need for a dipole magnet to get rid of residual electrons in the output beam is also investigated. Besides conversion efficiency, the simulation of different scatter foil thicknesses will also enable us to investigate the dependence of the beam divergence upon this parameter. Radiation protection is another important design goal that can take advantage of our application. More specifically, we will study the dose distribution around the chamber which main contribution comes from back-scattered electrons by scatter foil and other collimation elements, as well as potential contributions of neutrons produced by photonuclear reactions from the high energy tails of the X-ray beam. The final project aims are design and optimization a proof-of-principle micro-CT/RT platform for small animals exploiting the unique features of a novel concept all-optical bremsstrahlung X-ray beam. This research was supported by theItalian Ministry of Research (MIUR) within the PRIN project "PRELUDE" (PRIN-2015, n.20154F48P9).